Difusión de la gastronomía de las parroquias surorientales del cantón Loja, periodo septiembre 2013- agosto 2014 - Leon Arboleda, Jessica Valeria (2016)
This research was born the following problem: How to design a magazine for the dissemination of the cuisine of the south eastern parishes of the canton Loja? To channel the investigation was necessary to consider the following general objective: Design dissemination plan gastronomy of south eastern parishes of the canton Loja. The basis of the research was substantiated with theoretical extraction informant’s quality, for example: Business owners linked to gastronomy, representatives of the autonomous governments of the parishes involved, a representative of the Tourism Unit of the Municipality of Loja and an official of the Ministry of Tourism (based Loja). The deductive, inductive, scientific analytical method was used in the research process - synthetic, descriptive, historical, statistical; which helped to fulfill the objectives. Also, the techniques used were observation, interviews and survey successfully reached several conclusions and recommendations. Consequently, a socialization of the proposal raised in this paper was carried out to secure it. The proposal details objectives, goals, economic feasibility, technical, location, structural part and product diffusion is the magazine called "Gastronomic".